استجابة الكلوبيولينات المناعية وبعض تراكيز الأكسدة ومضاداتها في الدم بعد الجهد الهوائي لدى أصحاب الوزن المثالي والزائد - احمد, أ.د. ديار مغديد; طاهر, أ.م.د. مریوان شفیق; عثمان, م کاروان حسین (Sulaimani Journal for Humanities, 2023)
The study research aims to identify: 1- The differences between the values of the pre and post-tests for study with ideal weight in immunoglobulins and some concentrations of oxidants and their antioxidants in the blood after aerobic exercise. 2- The differences between the values of the pre and post-tests for overweight study in immunoglobulins and some concentrations of oxidants and their antioxidants in the blood after aerobic exercise. 3- The differences between the values of the post-tests between those with ideal weight and overweight in immunoglobulins and some concentrations of oxidants and their antioxidants in the blood after aerobic exercise. Forty male participants, who go to gym, in the governorate of Erbil volunteered to take part in the study, (20) of whom represent the ideal weight and (20) others represent overweight according to the BMI, with ages ranging from (22-28) years, and they were subjected to a (12-minute) running and walking test, then blood samples were drawn at two times, first was at rest (before the aerobic effort) and the second was post-test (post the aerobic effort). The volume of blood drawn for each time (7 millilitres) for each member of the sample, put the blood drawn in a sterile tube with a cover (Gel & Clot Activator) and leave it until coagulation at room temperature, then put it inside the centrifuge and start rotating at a speed of (3000) revolutions/min for (10-15 minutes) to obtain blood serum (serum), then the serum was withdrawn by means of a microdropper (micropipette), and it was distributed to five tubes of Eppendorf tubes and kept in the freezer at a temperature of (-20 °C) until use and for the following examinations: - Estimation of the total level of immunoglobulins IgA, IgG, and IgM. Estimation of the level of oxidation and antioxidants MDA, SOD, GSH, CAT, and TAOC. In light of the statistical treatments of the research results, the researcher reached the following